Microsatellite markers related to resistance of cocoa tree against witches’-broom - Santos, Rogério Mercês Ferreira; Lopes, Uilson Vanderlei; Bahia, Rita de Cássia; Machado, Regina Celle Rebouças; Ahnert, Dário; Corrêa, Ronan Xavier (Pesquisa Agropecuaria Brasileira, 2007)
The objectives of this work were to evaluate cocoa tree resistance against witches'-broom, in plants originated from the crossing between TSH 1188 and CCN 51 (segregating population), by means of two methods of inoculation in field conditions, and to identify microsatellite markers specific for resistant and susceptible plants. The control plants bore identical symptoms as the plants of the segregating population in 90% of the cases under the two methods. The method of artificial inoculation in the field allows the detection of false resistance to the disease. Of the 18 pairs of microsatellite primers amplified, 15 were polymorphic between genitors and six were polymorphic between the two groups of plants evaluated for resistance to witches'-broom. Three previously characterized markers were confirmed as associated to QTL (quantitative trait loci) related to resistance to the witches'-broom, which is common in other populations. Three new QTL for this characteristic, typical of this population, were also identified, which proves the utility of this population for cocoa breeding.